2005
DOI: 10.3354/meps289225
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and local temporal stability of population structure in the euphausiid Meganyctiphanes norvegica

Abstract: Meganyctiphanes norvegica (M. Sars 1856), the northern krill, is the largest and most abundant euphausiid species in the northern hemisphere, where it represents a key component of many pelagic communities. Although planktonic, krill could be considered a nektonic organism, as it is capable of active movements. This behaviour may be adaptive, because it allows these organisms to maintain their geographic position, leading to stable population structure, despite being continuously exposed to the heterogeneous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 36 publications
5
52
0
Order By: Relevance
“…The levels of genetic diversity observed from mtDNA (π = 0.003 to 0.005) are in the range reported 1 1 21 1 1 22 2 2 23 2 2 24 2 1 3 25 1 1 26 1 1 27 2 2 28 1 1 29 3 3 30 3 3 31 1 1 32 1 1 33 1 1 34 2 2 35 1 1 36 3 3 37 1 2 3 38 3 3 39 4 4 for other marine invertebrates in this area: 0.001 to 0.007 for Meganyctiphanes norvegica (Papetti et al 2005) and 0.001 to 0.005 for Sepia officinalis (Pérez-Losada et al 2007). The same observation was made for microsatellites (H e = 0.7 to 0.8, while, for example, the mean value found for Loligo forbesi was 0.8; Shaw et al 1999).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The levels of genetic diversity observed from mtDNA (π = 0.003 to 0.005) are in the range reported 1 1 21 1 1 22 2 2 23 2 2 24 2 1 3 25 1 1 26 1 1 27 2 2 28 1 1 29 3 3 30 3 3 31 1 1 32 1 1 33 1 1 34 2 2 35 1 1 36 3 3 37 1 2 3 38 3 3 39 4 4 for other marine invertebrates in this area: 0.001 to 0.007 for Meganyctiphanes norvegica (Papetti et al 2005) and 0.001 to 0.005 for Sepia officinalis (Pérez-Losada et al 2007). The same observation was made for microsatellites (H e = 0.7 to 0.8, while, for example, the mean value found for Loligo forbesi was 0.8; Shaw et al 1999).…”
Section: Discussionmentioning
confidence: 52%
“…Genetic distinctiveness of populations in these southern regions has been documented for other species within the NE Atlantic, for example, for the euphausiid Meganyctiphanes norvegica in Cádiz Bay (Zane et al 2000, Papetti et al 2005) and for the cuttlefish Sepia officinalis in the Canary Islands (Pérez-Losada et al 2007). But an absence of structure throughout the whole region has also been described for other species, like the European lobster Homarus gammarus (Triantafyllidis et al 2005) or the Norway lobster Nephrops norvegicus (Stamatis et al 2006).…”
Section: Discussionmentioning
confidence: 90%
“…Dispersal barriers in the open sea-Prior molecular work on marine holozooplankton has shown that genetic structure among populations is often quite high, despite early expectations that these populations would be genetically homogeneous (Papetti et al 2005;Chen and Hare 2011;Goetze 2011). However, very few studies have been conducted on oceanic species, and in many cases the spatial scale of sampling has been small relative to the species' distributional ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is often predicted that marine plankton will exhibit low population genetic structure even between geographically distant populations (Peijnenburg et al 2005;Provan et al 2009). However, many empirical studies have detected genetic structure over a range of spatial scales, including between ocean basins, between gyres within an ocean basin, and regionally among coastal embayments and estuaries (Papetti et al 2005;Blanco-Bercial et al 2011;Chen and Hare 2011). Additionally, genetic structure sometimes differs between holoplanktonic species collected at the same sites (e.g., Calanus spp.…”
mentioning
confidence: 99%
“…Diel or ontogenetic vertical migrations and their linkage to coastal currents are believed to support the retention of planktonic organisms within upwelling systems (Verheye and Field, 1992;Johnson, 2007;Parada et al, 2008;Harkins et al, 2013;Morgan, 2014;Moyano et al, 2014). Phylogeographic studies in other zooplankton species suggest that retention strategies also promote genetic differentiation (Papetti et al, 2005;Nuwer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%